Estudo e desenvolvimento de métodos de controle para microrredes CA ilhadas e conectadas à rede elétrica - Souza Junior, Marcus Evandro Teixeira (2020)
The objective of this work is to study AC microgrids, their control methods and their operation modes: islanded and grid-connected. Initially, a general presentation is made. The history of microgrids is briefly told and then their recent development is considered. The main concepts are dealt with. The many components that constitute a microgrid are detailed. Investigations on microgrids controls and architectures are followed. Standards about the subject are debated. The existing relationships among microgrids, power quality, ancillary services and smart grids are explored. After this universal approach, the control techniques for islanded and grid-connected operations become the work focus. For islanded microgrids, the requirements and the control proposals are commented. The inner controls, formed by Proportional-Resonant controllers, have their structures outlined. The islanded mode is only possible by the employment of the primary control that permits the parallel operation of inverters and the power sharing. For the present work, the conventional droop control method is the chosen one for this. It performs these functions in a simple, fast, flexible and without communication way. A single-phase AC microgrid is then described and designed, serving for analysis of the two modes of operation. Computational simulation results show the controls efficiency for the different working regimes, like load variations, inverters failures and load shedding. Some of the islanded mode difficulties, like frequency and voltage deviations and limitations on the power equilibrium, are healed in the grid-connected mode, which is the last topic of the work. All the conditions for the connection of a microgrid to the distribution grid are discussed. The elements that make the connection between the two systems, the synchronization techniques and the interconnection switch, are evaluated. A bibliographic revision about the control techniques for this mode is made. Finally, as the main contribution of this work, it is proposed a control method for synchronization, seamless transfer and connection of the microgrid to the power grid. The technique allows the complete active and reactive powers flow control between the microgrid and the distribution grid, being done individually for each converter. Computational simulations check and corroborate the control method proposed. The synchronization is realized for different grid phase-angle, frequency and voltage magnitude situations. The seamless transfer is verified. Power import and export, load changes, units exit, individual changes of production and power factor correction are some of the examined conjunctures. The return to the islanded mode is also exhibited. Process optimization, creation of an energy market, power quality enhancement, ancillary services provision and mitigation of environmental impacts are some of the available resources by the control and connection of the two systems.